Planeamiento en el Jardín Infantil - Ana Polanco-Hernández (Universidad Nacional, Costa Rica, 2003)
This article includes some strategies that can be helpful for didactics planning oriented to favoring integral development for initial level children. It also considers several options for an integral attention of children for the whole preschool stage, from zero to six years approximately, as well as some teacher characteristics necessary for teaching at this level. Furthermore, the article discusses three phases required for classroom planning: diagnosis and adaptation, development and closing. Finally, it proposes three planning models, considering development tasks, objectives and goals.